Interface of an old Version of Raman Spectrophotometer (Ramanor HG.2S JOBIN YVON) by LabVIEW - Abdelbary, Alakhib Ibrahim; Kafi, S. T. (International Journal of Online and Biomedical Engineering (iJOE), 2010)
In this work, the Raman spectrophotometer (HG.2S Jobin Yvon) was interfaced with labVIEW card to act as data acquisition system instead of the chart recorder. The interface of the Raman (HG.2S Jobin Yvon) with the labVIEW card require some modifications to the setup ,the main parts of the original setup of the systems were replaced by an air-cooled photomultiplier tube type (RCA IP28), log amplifier, handscanning and labVIEW card, all these components were assembled and the whole devices was tested successfully the new setup after interfacing by labVIEW was checked and calibrated by generating experiments with known standard solutions , which showed perfect consistency with literature in the references and published papers.